Efficacy of single and multi-strain probiotics on in vitro strain compatibility, pathogen inhibition, biofilm formation capability, and stress tolerance - Puvanasundram, Puvaneswari; Chong, Chou Min; Sabri, Suriana; Mohd Yusoff, Md Sabri; Lim, Keng Chin; Karim, Murni (Multidisciplinary Digital Publishing Institute, 2022)
Compatibility of each strain in a multi-strain probiotic (MSP), along with its properties, becomes a strong base for its formulation. In this study, single-strain probiotics (SSPs) and multi-strain probiotics (MSPs) were evaluated in vitro for strain compatibility, microbial antagonism, biofilm formation capacity, and stress tolerance. Bacillus amyloliquefaciens L11, Enterococcus hirae LAB3, and Lysinibacillus fusiformis SPS11 were chosen as MSP1 candidates because they showed much stronger antagonism to Aeromonas hydrophila and Streptococcus agalactiae than a single probiotic. MSP 2 candidates were Lysinibacillus fusiformis strains SPS11, A1, and Lysinibacillus sphaericus strain NAS32 because the inhibition zone produced by MSP 2 against Vibrio harveyi and Vibrio parahaemolyticus was much higher than that produced by its constituent SSPs. MSP1 in the co-culture assay reduced (p < 0.05) A. hydrophila count from 9.89 ± 0.1 CFU mL−1 to 2.14 ± 0.2 CFU mL−1. The biofilm formation of both MSPs were significantly higher (p < 0.05) than its constituent SSPs and the pathogens. The SSPs in both MSPs generally showed resistance to high temperatures (80, 90, and 100 °C) and a wide range of pH (2 to 9). This in vitro assessment study demonstrates that MSP1 and 2 have the potential to be further explored as multi-strain probiotics on selected aquatic species.